Improved Modulation Methods of the Dual-inverter Fed Open-end Winding Three-phase Motor Drives with Equal DC-link Voltage - Satiawan, I Nyoman Wahyu; Ida Bagus Fery Citarsa; Warindi; I Ketut Wiryajati; Supriono; Ni Made Seniari; I Made Budi Suksmadana (International Journal of Electrical, Energy and Power System Engineering, 2022)
This paper investigates PWM method for the dual-inverter fed open end winding three-phase induction motor drives. This is aimed to improve the quality of the output voltage as well as to enhance the motor performance by solving the drawback of the PWM method. The proposed PWM method operates two inverters in different technique, i.e one inverter operates in square wave mode (slow switching) and one inverter in PWM mode (fast switching). Although the PWM method can improve the quality of the inverter output voltage over the two-level inverter output, the proposed PWM method causes an excessive ripple in both torque and stator current especially at the transient period. The drawback is solved by applying a new switching strategy that manage the inverter switches operate in turn between slow switching and fast switching in one circle of operation. The proposed method is verified via simulation. The result shows that the quality of output voltages improves for all modulation indices in comparison with two-level inverter. Furthermore, torque ripple is reduced, and current ripple are improved as the current waveform is enhanced to be more symmetrical.